PENGARUH PENYULUHAN DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN ANEMIA DAN ASUPAN KONSUMSI ZAT BESI - N. Kordia Triana Dewi; Anak Agung Gde Raka Kayanaya; I Ketut Kencana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Poor iron consumption will cause anemia especially in young women. Therefore, iron consumption is very important to prevent anemia and they must get education about anemia and iron consumption then the knowledge of it will be increased. This education was done by video and aimed to determine the effect of media education in regards to increase knowledge of anemia and iron consumption for high school students in Denpasar. This type of research was a quasi experimental with a non equivalent control group design. There were 60 people as the number of samples. Respondents were divided into two groups: a treatment group of 30 samples and a control group of 30 samples. The study was conducted from February until April 2020 and questionnaire on anemia knowledge and iron consumption was used a data collection in this research. The results showed knowledge about anemia in the treatment group and the control group had increased, after being analyzed with Wilcoxon p = 0,000 and p = 0,000, then further analyzed using Mann Whitney obtained p = 0,000 (α 0.05). The results of iron consumption in the treatment and control groups increased, after being analyzed with Wilcoxon, p = 0.060 and p = 0.144, then further analyzed using Mann Whitney obtained p = 0.001 (α 0.05). It can be concluded that there was a significant effect of video education in increasing knowledge about anemia and iron consumption for high school students in Denpasar.Keywords: Knowledge of Anemia; Iron Consumption; Education